Triammine fac and mer Coordination for Ruthenium–Nitrosyl Complexes: Synthesis and Characterization of [RuNO(NH3)3Cl2]Cl. Issue 5 (9th February 2017) - Vorobyev, Vasily; Emelyanov, Vyacheslav A.; Plusnina, Olga A.; Makarov, Edgar M.; Baidina, Iraida A.; Smolentsev, Anton I.; Tkachev, Sergey V.; Asanova, Tatyana I.
Abstract : New high‐yielding methods for two [RuNO(NH3 )3 Cl2 ]Cl complexes are suggested. First, the ammine ligands are arranged facially through the reaction of a concentrated ammonia solution with the ruthenium–hexanitro complex. In the next step, the treatment of the previously unknown fac ‐Na[Ru(NO2 )3 (NH3 )3 ]· 3H2 O with hydrochloric acid leads to the nitrosyl complex. The mer ‐[RuNO(NH3 )3 Cl2 ]Cl· H2 O complex is formed from the corresponding aqua complex under reflux in 6m HCl. The complexes were studied by various methods [FTIR spectroscopy, 14 N NMR spectroscopy, extended X‐ray absorption fine structure (EXAFS), thermogravimetric analysis (TGA), and X‐ray diffraction studies]. Metastable states (Ru–O–N) were observed in mer ‐[RuNO(NH3 )3 Cl(H2 O)]Cl2, mer ‐[RuNO(NH3 )3 Cl2 ]Cl· H2 O, and fac ‐[RuNO(NH3 )3 Cl2 ]Cl under illumination at λ = 443 nm at liquid‐nitrogen temperatures. Abstract : Two isomeric ruthenium complexes are prepared, and efficient synthetic routes are demonstrated. The facial arrangement of the ammine ligands is defined by the synthesis of the previously unknown triamminetrinitroruthenate anion.